Enhanced ganoderic acids production by using thermotolerant Ganoderma tsugae at high-temperature liquid cultivation - Quan Ma; Yang-Meng-Jie Jing; Li-Yuan Luo; Xiao-Long He; Yue-Qin Liu (PLoS ONE, 2026)
Ganoderic acids (GAs) are bioactive triterpenoids produced by Ganoderma species with demonstrated anticancer properties. While the yield of GAs in Ganoderma tsugae is typically low, heat stress has been shown to enhance its production. This study employed atmospheric and room temperature plasma (ARTP) mutagenesis to develop thermotolerant G. tsugae mutants for high-temperature cultivation at 35°C. From 59 mutants generated, strain Ganoderma tsugae 9 (GT9) demonstrated superior thermotolerance, showing 51.48% increased mycelial growth rate and 76.03% higher biomass compared to wild-type (WT) at 35°C (one-way ANOVA with Dunnett’s test, p < 0.05). Physiological characterization revealed GT9 possessed enhanced membrane fluidity, elevated intracellular levels of lanosterol (92.49% increase), squalene (1.36-fold increase), trehalose, and ergosterol (66.98% increase) (two-way ANOVA with Tukey’s test, p < 0.05). Transcriptional analysis revealed significant upregulation of key GAs biosynthetic genes ( hmgr , sqs , se , ls ) and heat shock protein genes ( hsp17.4 , hsp22 , hsp70 , hsp90 ). After 10-day cultivation at 35°C, GT9 produced 1.01-fold more GAs than the WT at 35°C and 22.64% more than the WT at 25°C (two-way ANOVA with Tukey’s test, p < 0.05). However, the difference in GAs production between the WT strain cultured at 25°C and the GT9 strain cultured at 35°C was not significant. ARTP-generated thermotolerant G. tsugae mutants enable efficient high-temperature fermentation for enhanced GAs production. This strategy provides significant advantages for industrial-scale application while elucidating the physiological and molecular mechanisms underlying improved GAs biosynthesis under heat stress.